Analisis Keterkaitan Konsep Antropologi Pada Muatan IPS di Kelas 5 SD - Suci Rahayu (Pena Edukasia, 2024)
Anthropology, which is part of the social sciences that studies humans and their characteristics and culture in society, has developed rapidly in the world of education in the mid-20th century. Since then, many researches and studies on anthropology have continued to be developed with the intention that humans as members of society could be able to understand their role as biological and social beings better. The purpose of writing this paper is to know more about the scope of anthropology, to know the history and development of anthropology, to know the branches of anthropology and its relevance to other social sciences, and to know the implementation of learning anthropology in everyday life. This paper is written using the literature review method so that the author can understand and evaluate existing knowledge about the study of Anthropology and can develop a comprehensive understanding of various perspectives, theories and methodological approaches to the science of Anthropology.